Faktor-Faktor Yang Berhubungan Dengan Kejadian Stunting Pada Balita di Pekon Banjarmanis Gisting Tanggamus Tahun 2020 (Factors Associated with Incidence Toddlers Stunting in Pekon Banjarmanis Gisting Tanggamus 2020) - Saputra, Anggun; Rahmawati, Asri; Kurniawati, Desi (Universitas Muhammadiyah Yogyakarta, 2020)
Stunting (z-score TB / U <-2 SD) is a condition of failure to thrive due to lack of micro and macro nutrient intake for a long period of time or from the mother's womb. In addition, the lack of early prevention and proper management has made the incidence of stunting continue to increase and cause problems in children up to adulthood in terms of social, economic and health. This research was conducted to determinant factors associated with incidence toddlers stunting in Pekon Banjarmanis Gisting Tanggamus 2020. The method of research uses observasional analitik with cross sectional apporch. Sampling technique in this reaserch is taken with inclusion criteria by using cluster sampling technique, the sample in this reaserch consist of 52 respondents. Analysis statistic uses chi square with significant level p<0,05. The result of research shows there is correlation between the incidence of stunting with a history of exclusive breastfeeding (p = 0.025, OR: 5,600), family income (p = 0.038, OR: 0.288), feeding (p = 0,000, OR: 13,500), history of illness (p = 0.006, OR: 0.158) and there was no relationship between stunting and maternal knowledge about nutrition (p = 0.542, OR: 0.700), environmental sanitation and hygiene (p = 0.840, OR: 1.125). It be expected the community can increase intake of nutritional balanced for pregnant women and children, parenting children when healthy and sick, maintaining environmental sanitation and hygien, increasing knowledge about nutrition for parents to prevent the occurrence of stunting and nutritional disorders in children